دراسة مورفولوجية لمجتمعات الأكاروس الأحمر ذي البقعتين Tetranychus urticae Koch 1836 والأكاروس القرمزي Tetranychus cinnabarinus (Boisduval 1867) (Acari: Tetranychidae) على عوائل نباتية مختلفة في محافظة اللاذقية - صقر, ابراهيم عزيز; زريقي, غيث سعيد (Latakia University Journal -Biological Sciences Series, 2013)
إن اعتبار الأكاروس القرمزي Tetranychus cinnabarinus (Boisduval 1867) كنوع مستقل أو كمرادف لـ Tetranychus urticae Koch 1836 لا يزال قضية غير متفق عليها في مجال التصنيف. تم في المرحلة الأولى من الدراسة الحالية العمل على النوعين كنوع واحد، والوصف اعتماداَ على الصفات المورفولوجية المميزة عند كل من الذكر والأنثى، وفي المرحلة الثانية تم فصل النوعين اعتماداً على الصفات التصنيفية التي وضعها عدد من المصنفين الذين عدّوا T. cinnabarinus نوعاً مستقلاً. كما اختبر مدى تطابق بعض المقاييس المعتمدة للفصل بين هذين النوعين مع النماذج المحلية، حيث لم تنطبق تلك المقاييس على النماذج المحلية التي أبدت عدة اختلافات بالمقارنة معها. ولا تدعم النتائج الحالية فكرة النظر إلى كل من T. urticae وT. cinnabarinus كنوعين منفصلين. ـوجد كل من T. urticae وT. cinnabarinuc على نباتات مختلفة برية مزروعة في مناطق مختلفة من محافظة اللاذقية، ومن أصل 100 عينة نباتية مصابة بالأكاروسات، ووجد الأول على 29 عينة في حين وجد الثاني على 9 منها. The accuracy of the taxon T. cinnabarinus (Boisduval 1867) as a distinct species, or as a synonym of Tetranychus urticae Koch 1836, is still standing as a controversial issue of taxonomy and as a point of discussion. T. cinnabarinus and T. urticae have been regarded in the first stage of this study as one species, and it was characterized depending on the distinctive characteristics of both genders. In the second stage, the two species were distinguished according to many morphological characters that have been recommended by authors cited T.cinnabarinus as a valid species. The efficiency of some measures adopted to distinguish both T. cinnabarinus and T. urticae were also tested. Measurements didn't match local samples that showed obvious differences, T. cinnabarinus & T. urticae are not likely to be considered as two different species according to recent researches. Both T. cinnabarinus and T. urticae were detected on various wild and cultivated host plants. One hundred samples of plants presented symptoms of tetranychid attacks were collected from different localities in Lattakia province. Both T. urticae and T. cinnabarinus were found on 29, 9 samples, respectively.